The Utility of Exosomes in Diagnosis and Therapy of Diabetes Mellitus and Associated Complications - Sun, Yaoxiang; Tao, Qing; Wu, Xueqin; Zhang, Ling; Liu, Qi; Wang, Lei (Frontiers in Endocrinology, 2021)
Diabetes mellitus and the associated complications are metabolic diseases with high morbidity that result in poor quality of health and life. The lack of diagnostic methods for early detection result in patients losing the best treatment opportunity. Oral hypoglycemics and/or exogenous insulin replenishment are currently the most common therapeutic strategies, which only yield temporary glycemic control rather than curing the disease and its complications. Exosomes are nanoparticles containing bioactive molecules reflecting individual physiological status, regulating metabolism, and repairing damaged tissues. They function as biomarkers of diabetes mellitus and diabetic complications. Considering exosomes are bioactive molecules, can be obtained from body fluid, and have cell-type specificity, in this review, we highlight the multifold effects of exosomes in the pathology and therapy of diabetes mellitus and diabetic complications.